First‐in‐Human Studies of MW01‐6‐189WH, a Brain‐Penetrant, Antineuroinflammatory Small‐Molecule Drug Candidate: Phase 1 Safety, Tolerability, Pharmacokinetic, and Pharmacodynamic Studies in Healthy Adult Volunteers. Issue 2 (7th April 2020) - Van Eldik, Linda J.; Sawaki, Lumy; Bowen, Karen; Laskowitz, Daniel T.; Noveck, Robert J.; Hauser, Byron; Jordan, Lynn; Spears, Tracy G.; Wu, Huali; Watt, Kevin; Raja, Shruti; Roy, Saktimayee M.; et al.
Abstract: MW01‐6‐189WH (MW189) is a novel central nervous system–penetrant small‐molecule drug candidate that selectively attenuates stressor‐induced proinflammatory cytokine overproduction and is efficacious in intracerebral hemorrhage and traumatic brain injury animal models. We report first‐in‐human, randomized, double‐blind, placebo‐controlled phase 1 studies to evaluate the safety, tolerability, and pharmacokinetics (PK) of single and multiple ascending intravenous doses of MW189 in healthy adult volunteers. MW189 was safe and well tolerated in single and multiple doses up to 0.25 mg/kg, with no clinically significant concerns. The most common drug‐related treatment‐emergent adverse event was infusion‐site reactions, likely related to drug solution acidity. No clinically concerning changes were seen in vital signs, electrocardiograms, physical or neurological examinations, or safety laboratory results. PK analysis showed dose‐proportional increases in plasma concentrations of MW189 after single or multiple doses, with approximately linear kinetics and no significant drug accumulation. Steady state was achieved by dose 3 for all dosing cohorts. A pilot pharmacodynamic study administering low‐dose endotoxin to induce a systemic inflammatory response was done to evaluate the effects of a single intravenous dose of MW189 on plasma cytokine levels. MW189 treatment resulted in lower levels of the proinflammatory cytokine TNF‐α and higher levels of the anti‐inflammatory cytokine IL‐10 compared with placebo treatment. The outcomes are consistent with the pharmacological mechanism of MW189. Overall, the safety profile, PK properties, and pharmacodynamic effect support further development of MW189 for patients with acute brain injury.